Peran Hubungan Masyarakat dalam Meningkatkan Mutu Pendidikan - Dwi Kurniasari; Lukman Hakim; Muhammad Syaifudin (Journal on Education, 2024)
The role of public relations for educational institutions in the era of industrial revolution 4.0 has now become an integral part of the quality management of educational institutions. Public relations or public relations is the practice of managing the dissemination of information between individuals or organizations and the public. This research aims to determine the extent of the role of public relations (PR) in improving the quality of education. This research uses library research. Library research is a type of research that is closely related to scientific methods, theories, philosophical studies (philosophical approach), literary treasures and ready-made texts obtained as data sources with a library background. The results of this research are that Public Relations has a strategic role in efforts to improve the quality of educational institutions. With the existence of public relations, it is hoped that mutual understanding will occur, resulting in a good cooperative attitude between the community and the school to overcome educational problems faced by both parties. Efforts to improve the quality of education cannot be separated from community participation which is an important factor in supporting the achievement of programs organized in educational institutions